Social Roles in an Online Support Community for Older People - Pfeil, Ulrike; Svangstu, Knut; Ang, Chee Siang; Zaphiris, Panayiotis (My University, 2011)
In this article, an online support community for older people is studied, with the aim of developing a taxonomy of social roles based on content analysis and social network analysis. Four hundred messages (posted between August 9, 2007, and February 5, 2008) in an online support community for older people (http://www.seniornet.org) were investigated. The data were analyzed to identify and shed light on patterns of the online functional behavior as well as the social structure of active members. Drawing on the findings, a set of six social roles were identified, defined, and described in depth. The findings showed that the structural positions of online community members were associated with the kind of content these members tended to post. For example, it was found that central members were very likely to give support, whereas members not very well connected were more inclined to post self-disclosing messages.
Keywords: Websites; User interfaces; Web object